Amniotic Fluid Stem Cells from EGFP Transgenic Mice Attenuate Hyperoxia-Induced Acute Lung Injury - Wen, Shih-Tao (Public Library of Science, 2013)
High concentrations of oxygen aggravate the severity of lung injury in patients requiring mechanical ventilation. Although mesenchymal stem cells have been shown to effectively attenuate various injured tissues, there is limited information regarding a role for amniotic fluid stem cells (AFSCs) in treating acute lung injury. We hypothesized that intravenous delivery of AFSCs would attenuate lung injury in an experimental model of hyperoxia-induced lung injury. AFSCs were isolated from EGFP transgenic mice. The in vitro differentiation, surface markers, and migration of the AFSCs were assessed by specific staining, flow cytometry, and a co-culture system, respectively. The in vivo therapeutic potential of AFSCs was evaluated in a model of acute hyperoxia-induced lung injury in mice. The administration of AFSCs significantly reduced the hyperoxia-induced pulmonary inflammation, as reflected by significant reductions in lung wet/dry ratio, neutrophil counts, and the level of apoptosis, as well as reducing the levels of inflammatory cytokine (IL-1β, IL-6, and TNF-α) and early-stage fibrosis in lung tissues. Moreover, EGFP-expressing AFSCs were detected and engrafted into a peripheral lung epithelial cell lineage by fluorescence microscopy and DAPI stain. Intravenous administration of AFSCs may offer a new therapeutic strategy for acute lung injury (ALI), for which efficient treatments are currently unavailable.